2019
DOI: 10.1002/cbic.201900489
|View full text |Cite
|
Sign up to set email alerts
|

Effective Characterization of DNA Ligation Kinetics by High‐Resolution Melting Analysis

Abstract: High‐resolution melting (HRM) analysis has been improved and applied for the first time to quantitative analysis of enzymatic reactions. By using the relative ratios of peak intensities of substrates and products, the quantitativity of conventional HRM analysis has been improved to allow detailed kinetic analysis. As an example, the ligation of sticky ends through the action of T4 DNA ligase has been kinetically analyzed, with comprehensive data on substrate specificity and other properties having been obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…[ 19 ] (For sticky‐end ligation a high‐resolution melting analysis study indicated that only K m and not k cat was strongly affected by mismatches. [ 35 ] ) We reason that the temperature dependence of K m coupled with the temperature dependence of the nicked duplex association constant allows for the enhanced selectivity observed. Regarding the dependence of selectivity on the enzyme concentration, we propose that the higher enzyme concentration shifted the equilibria toward formation of the enzyme‐nicked duplex complex, which is why greater temperatures were required to destabilize the enzyme‐mismatched template duplex complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19 ] (For sticky‐end ligation a high‐resolution melting analysis study indicated that only K m and not k cat was strongly affected by mismatches. [ 35 ] ) We reason that the temperature dependence of K m coupled with the temperature dependence of the nicked duplex association constant allows for the enhanced selectivity observed. Regarding the dependence of selectivity on the enzyme concentration, we propose that the higher enzyme concentration shifted the equilibria toward formation of the enzyme‐nicked duplex complex, which is why greater temperatures were required to destabilize the enzyme‐mismatched template duplex complex.…”
Section: Resultsmentioning
confidence: 99%
“…[19] (For stickyend ligation a high-resolution melting analysis study indicated that only K m and not k cat was strongly affected by mismatches. [35] ) We complex. Finally, with respect to the abasic-containing system, the less ordered structure of the nicked duplex with the abasic site [36] might destabilize the enzyme-nicked duplex complex, leading to greater selectivity at lower temperatures with respect to the T m .…”
Section: Selectivity In Enzymatic Vs Chemical Ligationmentioning
confidence: 99%
“…The present findings should greatly widen the scope of the applications of Tth DNA ligase. In addition, our study also confirmed that HRM is a promising approach to analyze the DNA enzymatic reactions for which there is enough difference in T m between substrate and product . Still more detailed mechanistic studies on these factors are currently under way in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, cyclization can occur efficiently because even the 7-bp adapter (un-phosphorylated) can ligate to Ta/Tb with a yield higher than 80% (lane 7). It should be noted that this cyclization is carried out by the ligation of sticky ends with 5-nt long overhangs, which is much more efficient for T4 DNA ligase [20,21]. In the case of the 6-bp adapter, when the un-phosphorylated adapter was used, the ligation yield decreased to about 40% (Lane 5), and the yield remained 100% for the phosphorylated one.…”
Section: High Sensitivity Capture and Cyclization Of Target With Dyna...mentioning
confidence: 99%
“…Obviously, cyclization can occur efficiently because even the 7-bp adapter (un-phosphorylated) can ligate to Ta/Tb with a yield higher than 80% (lane 7). It should be noted that this cyclization is carried out by the ligation of sticky ends with 5-nt long overhangs, which is much more efficient for T4 DNA ligase [20,21]. The yields for target cyclization at low target concentrations (10 7 copies/µL) using the above three adapters were also analyzed by quantitative PCR (qPCR).…”
Section: High Sensitivity Capture and Cyclization Of Target With Dyna...mentioning
confidence: 99%